The heterogeneity of astrocytes in glaucoma - Yunjing Tang; Yunjing Tang; Yongjiang Chen; Danian Chen; Danian Chen (Frontiers Media S.A., 2022)
Glaucoma is a leading cause of blindness with progressive degeneration of retinal ganglion cells. Aging and increased intraocular pressure (IOP) are major risk factors. Lowering IOP does not always stop the disease progression. Alternative ways of protecting the optic nerve are intensively studied in glaucoma. Astrocytes are macroglia residing in the retina, optic nerve head (ONH), and visual brain, which keep neuronal homeostasis, regulate neuronal activities and are part of the immune responses to the retina and brain insults. In this brief review, we discuss the activation and heterogeneity of astrocytes in the retina, optic nerve head, and visual brain of glaucoma patients and animal models. We also discuss some recent transgenic and gene knockout studies using glaucoma mouse models to clarify the role of astrocytes in the pathogenesis of glaucoma. Astrocytes are heterogeneous and play crucial roles in the pathogenesis of glaucoma, especially in the process of neuroinflammation and mitochondrial dysfunction. In astrocytes, overexpression of Stat3 or knockdown of IκKβ/p65, caspase-8, and mitochondrial uncoupling proteins (Ucp2) can reduce ganglion cell loss in glaucoma mouse models. Based on these studies, therapeutic strategies targeting the heterogeneity of reactive astrocytes by enhancing their beneficial reactivity or suppressing their detrimental reactivity are alternative options for glaucoma treatment in the future.